Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/et-11-2018-0232
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation on learning and teaching lean manufacturing

Abstract: PurposeThis article identifies the association between two methods for teaching lean manufacturing (LM): problem-based learning (PBL) and classroom lectures, and students' learning styles of a postgraduate course.Design/methodology/approachData were collected from graduate students LM courses that present different teaching approaches. Thus, students' learning preferences were gathered through the application of the Index of Learning Style questionnaire, and their performance assessed after each course.Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…These practices have been widely evidenced in academic research (e.g. Lovejoy, 1998 ; Casado, 2000 ; Medina-López et al., 2011 ; Brandon-Jones et al., 2012 ; Tortorella and Cauchick-Miguel, 2018 ; Medini, 2018 ; Tortorella et al., 2020b ) and institutional reports (e.g. University of Exeter, 2020 ; New Castle University, 2020 ; and in the US by Lathan, 2020 ) related to teaching of Engineering and Business Management.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These practices have been widely evidenced in academic research (e.g. Lovejoy, 1998 ; Casado, 2000 ; Medina-López et al., 2011 ; Brandon-Jones et al., 2012 ; Tortorella and Cauchick-Miguel, 2018 ; Medini, 2018 ; Tortorella et al., 2020b ) and institutional reports (e.g. University of Exeter, 2020 ; New Castle University, 2020 ; and in the US by Lathan, 2020 ) related to teaching of Engineering and Business Management.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to statistical procedures, we conducted Harman´s single factor test ( Malhotra et al., 2006 ), which is one technique to identify common method variance, and its use has been evidenced in many survey-based studies with similar objectives (e.g. Marodin et al., 2018 ; Tortorella et al., 2020b ; Saurin et al., 2020 ). Results for this test indicated that 22.5% of the variance was represented by the first factor, which suggests that common method variance was not likely to be a problem because most of the variance was not loaded into one factor.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, students should be encouraged to develop an active position so that they can interact with other people and different contexts, contributing to improved learning. This fact is especially true when considering LM principles, which are somewhat abstract and difficult to be understood by a low-experienced audience (Tortorella and Cauchick-Miguel, 2017; Tortorella et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few papers have discussed teaching of Lean Manufacturing on the postgraduate academic level. Tortorella and Cauchick-Miguel [16,30] as well as Tortorella et al [31] have discussed integration of two teaching approaches to enhance the Lean Manufacturing (LM) learning at postgraduate courses and to verify their effectiveness by comparing students' performance and learning preferences. Their studies are focused on teaching effectiveness based on problem-based learning incorporated into traditional approaches.…”
Section: Postgraduate Courses On Lean Manufacturing (And Related)mentioning
confidence: 99%
“…The idea of using problem-based learning, experiential learning, or related approaches, however, seems logical at the first glance. Tortorella and Cauchick-Miguel [16,30] as well as Tortorella et al [31] have proved that it really is effective when applied to teaching LM, and that problem-based learning (PBL) may be an effective complementary method for LM learning. Their papers have also discussed associations between teaching methods and learning styles.…”
Section: Postgraduate Courses On Lean Manufacturing (And Related)mentioning
confidence: 99%